The New Normal, Adjuncts and Part-Time Instructors - Jeff Knox; Julie Rabun; Kim Hawkins (Academic Chairpersons Conference Proceedings, 2018)
Department chairs are under increasing pressure from administration to replace departing full-time professors with adjuncts. The chair is faced with a challenging environment that includes navigating personalities, workloads, student perception, varied commitment levels, and meeting accreditation standards. Strategies are discussed as participants share ideas to navigate this complicated issue.
Keywords: adjuncts; workloads; hiring; accreditation; retention